Host stage preference of Dolichogenidea tasmanica (Cameron, 1912) (Hymenoptera: Braconidae), a parasitoid of Epiphyas postvittana (Walker, 1863) (Lepidoptera: Tortricidae). Issue 3 (15th October 2014) - Yazdani, Maryam; Feng, Yi; Glatz, Richard; Keller, Michael A
Abstract E piphyas postvittana (Walker, 1863), or light brown apple moth (LBAM), is a highly polyphagous native Australian species and a major insect pest in Australian vineyards. Dolichogenidea tasmanica (Cameron, 1912) is the most abundant parasitoid of the larval stages of LBAM. The prime objective of our study was to determine the parasitism success of D. tasmanica on different larval stages of E. postvittana. Additionally, we aimed to find out if larval head capsule width could be used to determine the instar number by examining the variability in head capsule size of each instar of LBAM and the effect of rearing temperature on larval head capsule size. To determine which of the first three larval stages of LBAM parasitised is most effectively by D. tasmanica, choice and no‐choice tests were conducted in a wind tunnel. Head capsule widths varied with rearing temperature, especially in the final fifth or sixth instar. We showed that the ranges of head capsule widths overlaps between successive instars three through six, which makes it impossible to distinguish these instars of LBAM using head capsule size alone. We showed that first, second and third instars of LBAM are parasitised by D. tasmanica. No‐choice and choice tests revealed that there are significant differences in parasitism among the three susceptible instars, with the highest percentage of parasitism found in second instars in no‐choice and choice tests (65.1% and 65.8%, respectively) compared with first instars (61.1% and 45.1%) and third instars (27.3% and 37.5%). Wasps developed faster in third instars, but the wasp female's size was not significantly different among the instars attacked. These data confirm that D. tasmanica is capable of parasitising early larval instars, which is important for minimising damage through biological control.